Reprint of: Digital and spatial knowledge management in urban governance: Emerging issues in India, Brazil, South Africa, and Peru. (April 2015) - Baud, Isa; Scott, Dianne; Pfeffer, Karin; Sydenstricker-Neto, John; Denis, Eric
Abstract: The main question concerns the ways in which knowledge management configurations (KM) within urban governance are being transformed through digitization and spatializing information (GIS). This question fits into broader discussions on how knowledge construction, circulation and utilization can improve competences in local government (efficiency and effectiveness), make urban planning more knowledge-based, and provide greater recognition of citizens' knowledge (accountability). Local governments need such instruments in dealing with increasing complexity and uncertainty in urban development. We examine how uneven patterns of technological change in using ICT and GIS are transforming current local government work processes in terms of efficiency and effectiveness in their outcomes, utilizing empirical data from extended case studies in six medium-sized cities in India, South Africa, Brazil, and Peru, participating in the Chance2Sustain research network. Knowledge management in cities is configured through several dimensions: 1) discourses for digitizing KM in local urban development; 2) actor networks producing socio-spatial knowledge; 3) embedding KM in decision-making processes (power struggles, exclusion); and 4) influences of KM on work practices and interfaces with citizens. The case study results show that 1) KM discourses concerned four issues: strategic urban planning and integrated land use planning; determining geographic boundaries in urban development discourses; streamlining work processes of local governments, and mapping poverty and needs assessments; 2) initiatives mainly link government with the private sector at various scale levels; 3) codified and technical knowledge remains dominant in discussions on urban development; and 4) effects of KM are uneven, but improve work process efficiency, although the interface with citizens remains limited, focusing on middle-class relations to the exclusion of the poor. Highlights: Rationales for KM concern planning and land use issues. Initiatives link government and private sector. Codified and technical knowledge dominate urban development processes. KM improves work process efficiency. Interface with citizens remains limited.